Promosi Kesehatan Mata melaui Kegiatan Skrining Mata pada Siswa SMP di Kecamatan Wedung, Demak - Cahyo Wulandari; Rahmafari Fikra Maulida; Muhammad Asyam Fawwaz Akbar; Abdurrahman Nur Prasetyo (Direktorat Pengabdian kepada Masyarakat, 2024)
The eyes play an important role in a student's life. When eye problems occur, there can be a decrease in visual acuity, which can impact the student's quality of life. This can be characterized by blurry eyes when looking at the blackboard or looking far away. Student activities often involve prolonged staring at close objects, such as reading, doing assignments, or using devices such as smartphones and laptops. Without realizing it, these habits become a risk factor for a student to experience refractive error in the form of myopia, or nearsightedness. Students who experience myopia often do not realize it, so as an effort to maintain eye health, it is necessary to conduct eye screening to find out whether students experience refractive disorders or not, including in Wedung Subdistrict which is the location of KKN-PPM UGM unit JT-13. In order to carry out community service, eye screening is carried out for junior high school students. Located in 4 junior high schools in Wedung Sub-district, visual acuity (visus) was measured using the Snellen chart. A total of 300 junior high school students were examined, 55 of whom had decreased visual acuity. After each examination, students were educated on how to maintain eye health. In students with decreased visual acuity, risk factors were explored. This article is designed to describe how the eye health screening was conducted, the condition of some junior high school students with decreased visual acuity, and the risk factors that may cause refractive errors. Data collection was done by listing the results of each school's visus examination and history taking after the examination. The results of the visual acuity examination were analyzed using a descriptive quantitative method, while the interview data were analyzed using a qualitative method. Eye screening in junior high school students is expected to be a health promotion tool for both students with refractive errors and those without, as a reminder to maintain their eye health. For students with refractive errors, the screening can be a prelude to further examination so that students get immediate treatment, which can be in the form of refractive correction with the use of glasses, so that the refractive error that occurs doesn't getting worse.